PENGARUH PENGUMUMAN STRATEGI PENGUNGKAPAN INFORMASI EMITEN PADA RETURN SAHAM DI BURSA EFEK INDONESIA - SUPARTA WISADHA, I GEDE (Jurnal Ilmiah Akuntansi dan Bisnis, 2010)
The objective of this research is to the empirical test hyphotesis (1) theeffect of the information disclosures strategy to the stocks return.,(2) thelower average abnormal return after the announcement of informationdisclosures strategy then average abnormal return before of theannouncement it, (3) the lower average abnormal return after theannouncement of information disclosurse strategy then average abnormalreturn on the date of announcement it.The methodology of this research is expalanatory survey by usingsecondary data and 154 of listing companys at Indonesia StockExchanges as sample size, the sampling method used is a purposiverandom which category only the company sending the disclosures strategyto the Bapepam. The analysist data method is used the marketmodel(Markowitz) with the events study -3 days before and +3 days afterat the date announcement of disclosures strategy.The results of these research are (1) the effect of the informationdisclosures strategy to the stocks return is significantly.,(2) the loweraverage abnormal return after the announcement of informationdisclosures strategy then average abnormal return before of theannouncement has an empirical prove, (3) the lower average abnormalreturn after the announcement of information disclosures strategy thenaverage abnormal return on the date of announcement has an empiricalprove .The conclusion of this research are the results of these research isconsistently with the study before, however the assumption is used didnot the efficient market in the semi-strong form, but in the weak-formespecially for the Indonesia Capital Market.
Keywords: disclosures strategy, market model, the efficient market assumption.